2002
DOI: 10.1021/bp0255098
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Substrate Growth Kinetics of Leptothrix discophoraSP‐6

Abstract: The growth parameters of Leptothrix discophora SP-6 were quantified on the basis of the steady-state concentrations and utilization rates of pyruvate, dissolved oxygen, and concentration of microorganisms in a chemostat operated at 25 degrees C, pH 7.2, and an agitation rate of 350 rpm. The results showed that the microbial growth was limited by both pyruvate and dissolved oxygen. A combined growth kinetics model using Monod growth kinetics for pyruvate and Tessier growth kinetics for oxygen showed the best co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(15 reference statements)
2
8
0
Order By: Relevance
“…They also presented a K s with a 10% variability (between 0.45 and 0.5 mg·l -1 ) also quite similar to that presented in this work (ranging a 12% between 0.675 and 0.77 mg·l -1 ). The same can be said for the oxygen maintenance coefficient which is also consistent with the values presented for both attached growth systems (Zhou et al 2012) and suspended growth microorganisms (Yurt et al 2002). Thus, the methodology described in this current work represents progress in biofilm research, permitting the study and characterization of mass transport and biokinetics processes through in situ measurements while taking biofilm heterogeneity into consideration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They also presented a K s with a 10% variability (between 0.45 and 0.5 mg·l -1 ) also quite similar to that presented in this work (ranging a 12% between 0.675 and 0.77 mg·l -1 ). The same can be said for the oxygen maintenance coefficient which is also consistent with the values presented for both attached growth systems (Zhou et al 2012) and suspended growth microorganisms (Yurt et al 2002). Thus, the methodology described in this current work represents progress in biofilm research, permitting the study and characterization of mass transport and biokinetics processes through in situ measurements while taking biofilm heterogeneity into consideration.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, various studies (Liu and Chen 2009;Yurt et al 2002) have demonstrated the viability of the Monod kinetic equation, widely used in suspended cultures growth models (Brouwer et al 1998), to describe immobilized microbial growth.…”
Section: Biofilm Modelingmentioning
confidence: 99%
“…Minimizing this objective function was required to calculate the biokinetic parameters from the experimental data [16]. To improve the accuracy of the double parametric model, random data sets, similar to the experimental data, within the range of dissolved CO and H 2 tensions and calculated specific growth rates, were generated using standard Excel RAND function.…”
Section: Resultsmentioning
confidence: 99%
“…To prepare the inoculum, a MSVP plate (prepared with Agar Noble (Difco 0142)) was streaked with a frozen stock culture of Leptothrix discophora SP-6 as described by Yurt et al (31). Once the bacteria formed colonies, a single colony was transferred aseptically to 100 mL of MSVP medium in a flask.…”
Section: Methodsmentioning
confidence: 99%